(untitled) (BSAA arte, 2023)
In this article, a pseudo-Flemish triptych painted towards the end of the 19th century or the beginning of the 20th century by Joseph Van der Veken (1872-1964), a restorer, copyist and forger from Antwerp, known worldwide for his skill in reproducing Flemish paintings, is presented. The realization of this work is part of the context of revaluation of the Flemish painting of the 15th and 16th centuries, which generated a large-scale production of forgeries due to the great demand in the European market. These spurious works were also sold in Spain, reaching important collections and going unnoticed by expert eyes. In the case at hand, the Van der Veken triptych, then owned by the collector Francisco de Paula Arróspide Álvarez, XIII Count of La Revilla, was exhibited as an original at the Barcelona International Exhibition of 1929.